PENGARUH FEE AUDIT, MASA PERIKATAN AUDIT, DAN KOMITMEN ORGANISASI TERHADAP KUALITAS AUDIT (SURVEY PADA KANTOR AKUNTAN PUBLIK KOTA BANDUNG) - suryaningsih (PROGRAM STUDI AKUNTANSI - UNIVERSITAS MUHAMMADIYAH KUPANG, 2020)
This study aims to obtain empirical evidence of the influence of audit Fee, Audit EngagementPeriod and Organizational Commitment either simultaneously or partially to audit quality atpublic accounting firm in Bandung. Data collection method is questionnaire method withmeasurement technique used is Summated Rating Method: Likert Schale (likert scale). Dataanalysis techniques used in the form of Multiple Linear Regression Analysis. The results achievedin this study, that based on F test there is a significant influence between audit fees, auditengagement period and organizational commitment to audit quality at public accounting firm inBandung. While based on t concluded that only variable audit engagement period that does nothave a significant effect on audit quality. Meanwhile, the variable of audit fee and organizationalcommitment have positive and significant impact to audit quality.